2017
DOI: 10.4258/hir.2017.23.4.293
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Principal Diagnoses in Discharge Summaries and ICD-10 Coding Assessments Based on National Health Data of Thailand

Abstract: ObjectivesThis study examined the validity of the principal diagnoses on discharge summaries and coding assessments.MethodsData were collected from the National Health Security Office (NHSO) of Thailand in 2015. In total, 118,971 medical records were audited. The sample was drawn from government hospitals and private hospitals covered by the Universal Coverage Scheme in Thailand. Hospitals and cases were selected using NHSO criteria. The validity of the principal diagnoses listed in the “Summary and Coding Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
(12 reference statements)
0
8
0
1
Order By: Relevance
“…The study of validity of principle diagnoses from NHSO database in 2015 showed the level of agreement comparison of the codes for principle diagnoses given in the discharge summaries with the computerized ICD-10 codes in category "Disease of the nervous system" was 56.7%. 26 The third limitation was that diagnosis relied on ICD10 codes, which may have led to miscoding or misclassification bias. Our study's main strengths were that it was the first to estimate the incidence rate of GBS in Thailand using data from a nationwide administrative database and that our findings provide an overall background of GBS epidemiology.…”
Section: Treatments and Outcomes Of Gbsmentioning
confidence: 99%
“…The study of validity of principle diagnoses from NHSO database in 2015 showed the level of agreement comparison of the codes for principle diagnoses given in the discharge summaries with the computerized ICD-10 codes in category "Disease of the nervous system" was 56.7%. 26 The third limitation was that diagnosis relied on ICD10 codes, which may have led to miscoding or misclassification bias. Our study's main strengths were that it was the first to estimate the incidence rate of GBS in Thailand using data from a nationwide administrative database and that our findings provide an overall background of GBS epidemiology.…”
Section: Treatments and Outcomes Of Gbsmentioning
confidence: 99%
“…For discharged patients, the principal diagnosis refers to the final diagnosis confirmed after examination to diagnose the disease. It is the most important disease that requires a doctor's visit or treatment [19,20]. Sometimes, a new disease, not related to this, is discovered, and the additional disease that requires a lot of medical resources is selected as the principal diagnosis [19,20].…”
Section: Principal Diagnosis and Comorbiditiesmentioning
confidence: 99%
“…It is the most important disease that requires a doctor's visit or treatment [19,20]. Sometimes, a new disease, not related to this, is discovered, and the additional disease that requires a lot of medical resources is selected as the principal diagnosis [19,20]. Therefore, the principal diagnosis is an important medical condition that must be registered during hospitalization [21].…”
Section: Principal Diagnosis and Comorbiditiesmentioning
confidence: 99%
“…We selected encounters using ICD-9 codes. However, these codes have been criticized in the literature due to lack of clear definitions [ 26 27 ]. Future studies are needed that overcome this limitation by using more precise methods of identifying patients at risk for sepsis.…”
Section: Discussionmentioning
confidence: 99%